KOMPARASI KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SAAT PANDEMI COVID-19 - Celine, Celine; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2025)
The COVID-19 pandemic has had a massive impact on the world economy, including in Indonesia. This research was conducted to identify and analyze differences in financial performance in consumer non-cyclicals companies listed on the Indonesia Stock Exchange before and during the COVID-19 pandemic. Financial performance is measured using 4 ratios, i.e the liquidity ratio (current ratio), leverage ratio (debt to equity ratio), profitability ratio (return on assets), and activity ratio (total asset turnover). The sample in this research were 64 companies from 2018 to 2021 using a purposive sampling method. Data processing uses the IBM SPSS Statistics 26 application tool. Hypothesis testing is carried out using the Wilcoxon Signed Rank test. The results of this study are that there is a significant difference between before and during the COVID-19 pandemic in the leverage ratio (debt to equity ratio) and activity ratio (total asset turnover). In contrast to the results on the liquidity ratio (current ratio) and profitability ratio (return on assets) which showed no significant difference between before and when the COVID-19 pandemic occurred. The implication of this research is that companies are expected to pay attention to sales strategies to improve financial performance for the better which will give a positive signal to investors.